ANALISIS EKONOMI DIGITAL DAN TEKNOLOGI BLOCKCHAIN TERHADAP RETURN SAHAM PADA SEKTOR TEKNOLOGI DI BURSA EFEK INDONESIA - Ni Kadek Dwi Widiantari; Ni Luh Kardini; Ni Putu Yuli Tresna Dewi (Nusantara Hasana Journal, 2024)
This study examines the impact of Digital Economy and Blockchain Technology on stock Returns for technology companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. Using multiple linear regression analysis, the research finds that both Digital Economy and Blockchain Technology positively and significantly influence stock Returns. The statistical tests show that Digital Economy has a significant positive effect with a significance level of 0.002, and Blockchain Technology also demonstrates a significant positive impact with the same significance level. Additionally, the F-test confirms that these variables together have a significant effect on stock Returns. The results suggest that improvements in Digital Economy and effective application of Blockchain Technology can enhance stock Returns for technology firms. This study contributes to understanding the role of these variables in influencing stock performance and provides insights for investors and managers.